The Dynamic Growth and Chemical Change of Mixed Cultures Inoculation on Tapioka Fermentation (Indonesian Society for microbiology, 2017)
Lactobacillus plantarum and Saccharomyces cerevisiae possess several of extracellular and intracellular of enzymes beneficial to cassava fermentation. Tapioka (cassava starch) has limited uses in food industries due to its low pasting properties, therefore, biomodification by the use of fermentation is needed. The research was aimed to monitor the growth of Saccharomyces cerevisiae and L. plantarum during tapioca fermentation, and to evaluate the chemical change, of the fermented tapioka. Mixed cultures was inoculated at the designed concentration into tapioca suspension and incubated at room temperature (30Â±2oC) in facultative aerobic condition for 0, 24, 48, 60, 72, 96, 120, and 144 h. The growth change of S.cerevisiae and L. plantarum was monitored, and the change of pH, residual sugar, and starch granule was investigate. The result showed that S. cerevisiae had longer lag phase as well as stationary than L. plantarum was; nevertheless, they both reached log phase at the same time. Co-inoculated mixed cultures did not affect the change on pH and reducing sugar but increased pronouncely protein content at stationary period. Besides, there was sign of erosion to the structure of cassava starch granules which was an indication of changes in the pasting property of the cassava starch.Â